A Holistic Approach to Ship Design Volume 1: Optimisation of Ship Design and Operation for Life Cycle - Papanikolaou, Apostolos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces a holistic approach to ship design and its optimisation for life-cycle operation. It deals with the scientific background of the adopted approach and the associated synthesis model, which follows modern computer aided engineering (CAE) procedures. It integrates techno-economic databases, calculation and multi-objective optimisation modules and s/w tools with a well-established Computer-Aided Design (CAD) platform, along with a Virtual Vessel Framework (VVF), which will allow virtual testing before the building phase of a new vessel. The resulting graphic user interface (GUI) and information exchange systems enable the exploration of the huge design space to a much larger extent and in less time than is currently possible, thus leading to new insights and promising new design alternatives. The book not only covers the various stages of the design of the main ship system, but also addresses relevant major onboard systems/components in terms of life-cycle performanceto offer readers a better understanding of suitable outfitting details, which is a key aspect when it comes the outfitting-intensive products of international shipyards. The book disseminates results of the EU funded Horizon 2020 project HOLISHIP (www.holiship.eu).
Introduction to the HOLISHIP Project -- State of the Art: Ship Design for Life-Cycle -- Holistic Ship Design Optimisation -- The CAESES Design Software Platform -- The CPACS Design Software Platform -- Systemic Approach to Ship Design -- Tools for the Assessment of Ship Design and Operation -- Hydrodynamic Tools -- Structural Design Tools -- Produceability Tools -- Machinery and Equipment -- Energy efficiency of integrated machinery systems -- Economy -- Application Studies -- Index.
Keywords: Engineering design; Transportation engineering; Traffic engineering; Computer-aided engineering; Mathematical optimization; Fluid mechanics; Engineering Design; Transportation Technology and Traffic Engineering; Computer-Aided Engineering (CAD, CAE) and Design; Optimization; Engineering Fluid Dynamics